Cervical osteomyelitis caused by Burkholderia cepacia after rhinoplasty - Lenny Weinstein, Christin A. Knowlton, Miriam A. Smith (The Journal of Infection in Developing Countries, 2008)
Burkholderia cepacia, previously known as Pseudomonas cepacia, has been implicated in vertebral osteomyelitis in patients who are intravenous drug abusers. We report a case of acute vertebral osteomyelitis in a non-intravenous drug user, following an elective rhinoplasty.